Development of SDLC Framework for Financial Technology Project Management in Banking Institutions - Evania Raihan; Dyah Lestari Widaningrum (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: The rapid expansion of agent banking in Indonesia has increased the need for reliable and timely delivery of financial technology applications. The choice of Software Development Life Cycle (SDLC) methodology plays a critical role in project schedule performance, yet empirical comparisons particularly involving hybrid approaches within regulated banking environments remain limited. Objective: This study analyzes the impact of SDLC methods on project time performance in IT application development, with particular attention to the testing phase as a recurrent source of delay. Method: A quantitative comparative design was applied to 18 internal IT projects conducted in 2025 using Waterfall and Agile methodologies across Android-based EDC applications, mobile apps, and web systems. Independent-samples t-tests were used to examine differences in Schedule Performance Index (SPI), actual project duration, and delay. A phase-selective Hybrid SDLC was subsequently implemented in the EDC Android v1.0.5 project, applying Agile practices in testing while maintaining Waterfall in other phases. Result: Statistically significant differences were found between Agile and Waterfall across all time performance indicators, with Agile demonstrating superior schedule outcomes. The hybrid implementation further improved performance, reflected by an SPI greater than 1 and reduced testing duration. Conclusion: A phase-selective Hybrid SDLC provides an effective strategy to enhance schedule performance, particularly when testing is a bottleneck. The findings support selective SDLC adoption based on phase-specific characteristics. Limitations include the single-institution scope and absence of cost and quality metrics, suggesting directions for future multi-institutional research.